Uptake, translocation and biotransformation kinetics of BDE-47, 6-OH-BDE-47 and 6-MeO-BDE-47 in maize (Zea mays L.). (January 2016) - Xu, Xuehui; Wen, Bei; Huang, Honglin; Wang, Sen; Han, Ruixia; Zhang, Shuzhen
Abstract: This study presents a detailed kinetic investigation on the uptake, acropetal translocation and transformation of BDE-47, 6-OH-BDE-47 and 6-MeO-BDE-47 in maize ( Zea mays L.) by hydroponic exposure. Root uptake followed the order: BDE-47 > 6-MeO-BDE-47 > 6-OH-BDE-47, while 6-OH-BDE-47 was the most prone to acropetal translocation. Debromination rates of BDE-47 were 1.31 and 1.46 times greater than the hydroxylation and methoxylation rates, respectively. Transformation from BDE-47 to lower brominated OH/MeO-PBDEs occurred mainly through debromination first followed by hydroxylation or methoxylation. There was no transformation from 6-OH-BDE-47 or 6-MeO-BDE-47 to PBDEs. Methylation rate of 6-OH-BDE-47 was twice as high as that of 6-MeO-BDE-47 hydroxylation, indicating methylation of 6-OH-BDE-47 was easier and more rapid than hydroxylation of 6-MeO-BDE-47. Debromination and isomerization were potential metabolic pathways for 6-OH-BDE-47 and 6-MeO-BDE-47 in maize. This study provides important information for better understanding the mechanism on plant uptake and transformation of PBDEs. Graphical abstract: Highlights: Uptake and translocation of BDE-47 and 6-OH/MeO-BDE-47 were analog-specific. Debromination was the fast and dominant metabolic reaction of BDE-47 in maize. Metabolic pathways of BDE-47, 6-OH/MeO-BDE-47 in maize were discussed. Metabolic processes should be considered in exploring phytoremediation strategy. Abstract : This article provides direct in vivo evidences of bioaccumulation and biotransformation of PBDEs, OH-PBDEs and MeO-PBDEs in plants.